1997
DOI: 10.1042/cs0920415
|View full text |Cite
|
Sign up to set email alerts
|

Mild Endotoxaemia and the Inflammatory Response Induced by a Marathon Race

Abstract: 1. To address the question of whether endotoxaemia could be involved in the inflammatory response induced by long-term strenuous exercise, 18 male marathon runners [mean age 41 +/- 2 (SEM) years] were studied. Their performance in the marathon ranged from 2 h 46 min to 4 h 42 min. 2. Four venous blood samples were drawn: at rest, just before the race (baseline); within 15 min following the completion of the marathon; after 1 h of recovery; and the morning after the race. 3. The following humoral markers of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
91
4
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 14 publications
12
91
4
1
Order By: Relevance
“…A very low-CHO diet implies a very high-fat dietary content, which has been shown detrimental to immune function. We expected to find an increase in IL-6 from baseline following exercise in both dietary conditions, as previously reported in measurements taken after light, moderate and hard intensity exercise performed for short-and long-periods of time [2,7,12,22,27,34,40,51]. In our study, IL-6 increased significantly from baseline immediately following the duathlon regardless of the diet, and remained elevated 1-and 2-h following exercise.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A very low-CHO diet implies a very high-fat dietary content, which has been shown detrimental to immune function. We expected to find an increase in IL-6 from baseline following exercise in both dietary conditions, as previously reported in measurements taken after light, moderate and hard intensity exercise performed for short-and long-periods of time [2,7,12,22,27,34,40,51]. In our study, IL-6 increased significantly from baseline immediately following the duathlon regardless of the diet, and remained elevated 1-and 2-h following exercise.…”
Section: Discussionsupporting
confidence: 68%
“…This exercise intensity caused bacterial translocation immediately following exercise similar to that reported in marathon and ultra-endurance events [3,4,6,7,27,44].…”
Section: Discussionsupporting
confidence: 55%
“…Recent analysis using intracellular staining confirmed that CD14 ϩ CD16 ϩ monocytes are major producers of TNF-␣ and possess a higher sensitivity for LPS-induced TNF-␣ production in vivo compared with CD14 ϩϩ CD16 Ϫ monocytes (6,62,64). Therefore, it seems plausible that CD14 ϩ CD16 ϩ monocytes are responding to mild endotoxemia accompanying strenuous exercise (9,50) or EHS (68). A common finding when examining intracellular cytokine profiles with exercise, with or without hyperthermia, has been either no change or a slight reduction in the level of spontaneous TNF-␣ in cytokine-positive peripheral blood monocytes in trained (74,77,89) and untrained subjects (84), similar to the present study's responses in CD14 ϩϩ CD16 Ϫ monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma endotoxin concentration is associated with various activities such as alcohol consumption and with gastrointestinal distress after strenuous exercise or general anesthesia [89,[225][226][227]. In otherwise healthy individuals, stress, pharmaceuticals, toxicants, and dietary alterations together or individually can increase plasma endotoxin by enhancing gut permeability and/or by reducing clearance by liver macrophages [reviewed in 228].…”
Section: Discussionmentioning
confidence: 99%
“…However, both fibrinogen and factor X bind to PMNs in vitro [221,222]. Furthermore, fibrinogen inhibits PMN chemotaxis in vitro [223], and a peptide derived from factor X can bind to CD11b/CD18 on PMNs and inhibit transendothelial migration [226]. In this scenario, the reduced concentration of fibrinogen in plasma between 2 and 6 h of endotoxemia might free CD11b/CD18 for ICAM-1 binding and thereby promote adhesion and migration.…”
Section: Nitric Oxide (No)mentioning
confidence: 99%